The Influence of Earning Management, Dividend Policy, and Free Float Ratio on Stock Returns - Alifi, Alfin; Kurniawati, Lestari (Yayasan Ilomata, 2024)
Analysis of company performance is one of the considerations for investors in making investment decisions. Several issues related to earnings management arise due to the flexibility in accounting standards application becomes an investor’s special concern in analyzing financial statements. On the other side, investors’ attention to dividend distribution has various effects on several studies. Another issue that also attracts the investors’ attention is the new rules of minimum free float ratio for companies listed on the IDX to be 7.5% in 2019. Based on this phenomenon, this study aims to examine the effect of earnings management, dividend policy, and the ratio of free float to returns stock. The sample used is the property and real estate sector companies. This study uses the Fixed Effect Model with control variables in the form of profitability and firm value. The results show that earnings management significantly negatively affects returns, while dividend policy and free float have no significant effect on returns stock. Simultaneous research results also show a significant effect on returns with a coefficient of determination of 36.5%. As an implication, the results can be a reference for early identification of earnings management using existing financial report data. In terms of dividend policy, this research shows that dividend policy does not have a significant influence. However, considering the data in the research, investors can consider the pattern of dividend distribution amounts for each sector in making their investment decisions. The free float ratio variables show an insignificant effect on stock returns. However, research on the free float ratio in Indonesia is still limited.